3(4x+3)=2-5(7-x)

Simple and best practice solution for 3(4x+3)=2-5(7-x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(4x+3)=2-5(7-x) equation:


Simplifying
3(4x + 3) = 2 + -5(7 + -1x)

Reorder the terms:
3(3 + 4x) = 2 + -5(7 + -1x)
(3 * 3 + 4x * 3) = 2 + -5(7 + -1x)
(9 + 12x) = 2 + -5(7 + -1x)
9 + 12x = 2 + (7 * -5 + -1x * -5)
9 + 12x = 2 + (-35 + 5x)

Combine like terms: 2 + -35 = -33
9 + 12x = -33 + 5x

Solving
9 + 12x = -33 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
9 + 12x + -5x = -33 + 5x + -5x

Combine like terms: 12x + -5x = 7x
9 + 7x = -33 + 5x + -5x

Combine like terms: 5x + -5x = 0
9 + 7x = -33 + 0
9 + 7x = -33

Add '-9' to each side of the equation.
9 + -9 + 7x = -33 + -9

Combine like terms: 9 + -9 = 0
0 + 7x = -33 + -9
7x = -33 + -9

Combine like terms: -33 + -9 = -42
7x = -42

Divide each side by '7'.
x = -6

Simplifying
x = -6

See similar equations:

| 164x-82=738 | | 7(3x+1)=3x-8x | | 0.02x+0.5=0.35x+1.2 | | 5x+1=-13x+15 | | 2z+96=15z-85z | | 21x^2=7x | | x^2+2i=0 | | an=5n-8 | | -9+90=9x-90 | | 5x-95=x | | -8y-2=-7y-7 | | 3-4x+6-7=42 | | lnx=0.85 | | x^2+12x=540 | | 4(x-3)+2x=10 | | 1+15=-4(4x-4) | | 7x+9y=3+9x | | 30x^2+273x-270=0 | | m+11/8=8 | | 1+15=4(4x-4) | | 15x-5=25x+3 | | 2(x-3)+10=18 | | -4(x+1)-14=16+2 | | x+7+4x-3=3x+x-2x+16 | | 5k-3/(-3) | | y=-(1/3)x | | y=7000x+b | | 5k-3/3 | | 5k-3/-33 | | y=7000x | | 2(3x+9)=29+35 | | 4b^3(2b^4-10b^3+3)= |

Equations solver categories